Novel and recurrent TRPV4 mutations and their association with distinct phenotypes within the TRPV4 dysplasia family. Issue 10 (24th June 2010) - Dai, J; Kim, O-H; Cho, T-J; Schmidt-Rimpler, M; Tonoki, H; Takikawa, K; Haga, N; Miyoshi, K; Kitoh, H; Yoo, W-J; Choi, I-H; Song, H-R; et al.
Abstract : Background: Mutations in TRPV4, a gene that encodes a Ca 2+ permeable non-selective cation channel, have recently been found in a spectrum of skeletal dysplasias that includes brachyolmia, spondylometaphyseal dysplasia, Kozlowski type (SMDK) and metatropic dysplasia (MD). Only a total of seven missense mutations were detected, however. The full spectrum of TRPV4 mutations and their phenotypes remained unclear. Objectives and methods: To examine TRPV4 mutation spectrum and phenotype−genotype association, we searched for TRPV4 mutations by PCR-direct sequencing from genomic DNA in 22 MD and 20 SMDK probands. Results: TRPV4 mutations were found in all but one MD subject. In total, 19 different heterozygous mutations were identified in 41 subjects; two were recurrent and 17 were novel. In MD, a recurrent P799L mutation was identified in nine subjects, as well as 10 novel mutations including F471del, the first deletion mutation of TRPV4 . In SMDK, a recurrent R594H mutation was identified in 12 subjects and seven novel mutations. An association between the position of mutations and the disease phenotype was also observed. Thus, P799 in exon 15 is a hot codon for MD mutations, as four different amino acid substitutions have been observed at this codon; while R594 in exon 11 is a hotspot for SMDK mutations. Conclusion: The TRPV4 mutation spectrum in MD and SMDK, which showed genotype−phenotype correlation and potential functional significance of mutations that are non-randomly distributed over the gene, was presented in this study. The results would help diagnostic laboratories establish efficient screening strategies for genetic diagnosis of the TRPV4 dysplasia family diseases.